Psycholinguistic Dimensions of Designing the Future by Adolescents and Youth - Dolynska, Lubov; Grinova, Olha (Lesya Ukrainka Eastern European National University, 2022)
In today's rapidly changing society, the ability of an individual to effectively design their future becomes highly important. It is the youth when a person acquires the ability to realize the project of their future. Constructing life goals and plans for their implementation by youth is carried out in the process of information exchange, life experience expansion and reflection of their semantic cognitions in social communications. The success depends on the characteristics of their image transformation into concepts, their statements' reflection, and their interpretation of other people's statements. The article aims to reveal the psycholinguistic features of designing the future by adolescents and youth. The method of the free association test, along with the method of assessing five-year intervals, was used for empirical research. 120 undergraduate and graduate students aged 17 to 21 from the National Pedagogical Drahomanov University, Ukraine, participated in the study held in 2021. Its results showed that most respondents created their goals mainly in marital, family, or professional modes. The objectives of spiritual growth and personal self-realization were autonomously constructed only by a few respondents. Participants with explicit nuclear semantic cognitions and corresponding associative fields, including altruistic associations, revealed prolonged, consistent, realistic structures of their life goals. In contrast, respondents with underdeveloped structures of semantic fields mostly created intermittent, time-limited structures of life goals with somewhat formal cognitions of satisfying their needs in the future.
Keywords: designing the future; life goals; semantic field; free association test; adolescents; young adults